Therapeutic interventions for families and children in the child welfare system - Pickover, Sheri (Springer Publishing Company, 2016)
Introduction to the child welfare system -- The child perspective -- The adult perspective -- Beginning therapy -- Assessment -- Diagnosis, medication, and child welfare -- Treating attachment -- Treatment for loss and transitions -- Treating trauma -- Behavior modification and social skills -- Engaging families in treatment -- Collaborating with professionals -- Burnout, countertransference, ethics, and wellness